2020
DOI: 10.2298/sos2001001f
|View full text |Cite
|
Sign up to set email alerts
|

Densification of ultra-refractory transition metal diboride ceramics

Abstract: The densification behavior of transition metal diboride compounds was reviewed with emphasis on ZrB 2 and HfB 2 . These compounds are considered ultra-high temperature ceramics because they have melting temperatures above 3000°C. Densification of transition metal diborides is difficult due to their strong covalent bonding, which results in extremely high melting temperatures and low self-diffusion coefficients. In addition, oxide impurities present on the surface of powder particles promotes coarsening, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…14 For these reasons, hot pressing (HP), direct current sintering (DCS), and variants of both employing in situ reactions have become the favored sintering method for producing phase pure UHTCs with relative density above 90%. [15][16][17][18][19] For the intermediate stage of sintering (0.65 < ρ relative < 0.90) of the Group IV diborides, activation energies that have been reported range from 140 to 695 kJ/mol for ZrB 2 , 56 to 774 kJ/mol of TiB 2 , and 96 kJ/mol for HfB 2 . 5,[20][21][22][23] In general, studies have concluded that finer initial particle size and increased pressures reduced activation energies, even though the value of activation energy should only depend on the densification mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 For these reasons, hot pressing (HP), direct current sintering (DCS), and variants of both employing in situ reactions have become the favored sintering method for producing phase pure UHTCs with relative density above 90%. [15][16][17][18][19] For the intermediate stage of sintering (0.65 < ρ relative < 0.90) of the Group IV diborides, activation energies that have been reported range from 140 to 695 kJ/mol for ZrB 2 , 56 to 774 kJ/mol of TiB 2 , and 96 kJ/mol for HfB 2 . 5,[20][21][22][23] In general, studies have concluded that finer initial particle size and increased pressures reduced activation energies, even though the value of activation energy should only depend on the densification mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Sintering to full density generally requires temperatures above 1900°C and applied pressures greater than 32 MPa 14 . For these reasons, hot pressing (HP), direct current sintering (DCS), and variants of both employing in situ reactions have become the favored sintering method for producing phase pure UHTCs with relative density above 90% 15–19 . For the intermediate stage of sintering (0.65 < ρ relative < 0.90) of the Group IV diborides, activation energies that have been reported range from 140 to 695 kJ/mol for ZrB 2 , 56 to 774 kJ/mol of TiB 2 , and 96 kJ/mol for HfB 2 5,20–23 .…”
Section: Introductionmentioning
confidence: 99%
“…While this alternative raw material has to have positive effect on the strength and durability of the concrete/mortar, it is preferable that this resource is of secondary nature (a waste or by-product) or at least economically sustainable primary raw material. So far various pozzolanic materials which can be used as cement replacement have been identified: fly ash, bottom ash, clayey materials, metakaolin, ground granulated blast furnace slag, municipal waste ash, rice husk ash, silica fume, etc [1][2][3][4][5]. Silicon dioxide products (silica fume, micro silica, nano silica, colloidal silica, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Densification of ZrB 2 -based ceramics typically requires temperatures of 2000 • C or higher. 22 Incorporation of combinations of boron carbide (B 4 C), carbon (C), and/or silicon carbide (SiC) particles increases the driving force for densification and limits grain growth, which can result in peak densification temperatures below 2000 • C. [23][24][25][26] Silicon nitride (Si 3 N 4 ) additions to ZrB 2 have been shown to reduce the densification temperature to ∼1700 • C to achieve near-full density by hot-pressing. [27][28][29] Transition metal disilicides, specifically MoSi 2 and ZrSi 2 , improve densification by forming an in situ liquid phase during processing, allowing for increased densification at significantly reduced temperatures (1400 • C to 1900 • C).…”
Section: Introductionmentioning
confidence: 99%
“…Densification of ZrB 2 ‐based ceramics typically requires temperatures of 2000°C or higher 22 . Incorporation of combinations of boron carbide (B 4 C), carbon (C), and/or silicon carbide (SiC) particles increases the driving force for densification and limits grain growth, which can result in peak densification temperatures below 2000°C 23–26 .…”
Section: Introductionmentioning
confidence: 99%